2021
DOI: 10.3389/fmicb.2021.660920
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Evolutionary Genomics of the Blautia Genus: Potential New Species and Genetic Content Among Lineages

Abstract: Blautia, a genus established in 2008, is a relevantly abundant taxonomic group present in the microbiome of human and other mammalian gastrointestinal (GI) tracts. Several described (or proposed) Blautia species are available at this date. However, despite the increasing level of knowledge about Blautia, its diversity is still poorly understood. The increasing availability of Blautia genomic sequences in the public databases opens the possibility to study this genus from a genomic perspective. Here we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Compared with the blank 24 h group, all samples could selectively promote the growth of Bacteroides, Megasphaera, Blautia, Agathobacter, Bifidobacterium, Lactobacillus, and so forth, and inhibit the expansion of Fusobacterium and Faecalibacterium. It found that Bacteroides, Megasphaera, and so forth were principally involved in carbohydrate fermentation and metabolism, which could explain the enrichment of these bacteria. , In addition, studies have reported that Blautia can regulate obesity and type 2 diabetes, while Agathobacter was symbiotic with Bifidobacterium, making it possible for them to obtain more acetate for producing butyrate. , Interestingly, Bifidobacterium and Lactobacillus, which are traditional probiotics, were enriched in all groups, although the RGI and DRGI groups were not as abundant as the traditional prebiotic (inulin and FOS) groups. The results showed that molecular weight had a considerable contribution to the regulation of intestinal flora.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Compared with the blank 24 h group, all samples could selectively promote the growth of Bacteroides, Megasphaera, Blautia, Agathobacter, Bifidobacterium, Lactobacillus, and so forth, and inhibit the expansion of Fusobacterium and Faecalibacterium. It found that Bacteroides, Megasphaera, and so forth were principally involved in carbohydrate fermentation and metabolism, which could explain the enrichment of these bacteria. , In addition, studies have reported that Blautia can regulate obesity and type 2 diabetes, while Agathobacter was symbiotic with Bifidobacterium, making it possible for them to obtain more acetate for producing butyrate. , Interestingly, Bifidobacterium and Lactobacillus, which are traditional probiotics, were enriched in all groups, although the RGI and DRGI groups were not as abundant as the traditional prebiotic (inulin and FOS) groups. The results showed that molecular weight had a considerable contribution to the regulation of intestinal flora.…”
Section: Resultsmentioning
confidence: 93%
“…51,52 In addition, studies have reported that Blautia can regulate obesity and type 2 diabetes, while Agathobacter was symbiotic with Bifidobacterium, making it possible for them to obtain more acetate for producing butyrate. 53,54 Interestingly, Bifidobacterium and Lactobacillus, which are traditional probiotics, were enriched in all groups, although the RGI and DRGI groups were not as abundant as the traditional prebiotic (inulin and FOS) groups. The results showed that molecular weight had a considerable contribution to the regulation of intestinal flora.…”
Section: ■ Materials and Methodsmentioning
confidence: 98%
“…Members of the taxonomic genus Blautia have a major impact on human health, due to their role in indigestible carbohydrate degradation and production of short‐chain fatty acids (SCFAs), which act as metabolic mediators between the microbiota and the host 24 . This bacteria is dominant in a healthy gastrointestinal tract, representing between 2% and 8% of the human gut microbiota, and has a correlation with several host physiological dysfunctions, such as obesity, diabetes, cancer and inflammatory diseases 24,25 . For example, it has been shown that its abundance is reduced in children with type 1 diabetes and in patients with colorectal cancer 26 .…”
Section: Discussionmentioning
confidence: 99%
“…24 This bacteria is dominant in a healthy gastrointestinal tract, representing between 2% and 8% of the human gut microbiota, and has a correlation with several host physiological dysfunctions, such as obesity, diabetes, cancer and inflammatory diseases. 24,25 For example, it has been shown that its abundance is reduced in children with type 1…”
Section: Discussionmentioning
confidence: 99%
“…78 Further, both species are widely used as probiotic strains. 78,79 To further determine the antibacterial activity against bacteria that comprise the human gut microbiota, we tested our compound against B. producta, 80 C. ramosum, 81 B. thetaiotaomicron, 82 A. caccae, 83 and E. coli MG1655. Compound 5a was completely inactive against all species tested up to the highest concentration evaluated.…”
Section: )mentioning
confidence: 99%